Le programme de protection des taux hypothécaires - Moreau, Rémi (Assurances)

(untitled) (HEC Montréal, 1984)
To respond to concerns Canadians have about the uncertainty of future mortgage costs, the last Federal Budget proposed different measures to give protection to homeowners and prospective home buyers; one of them is entitled the Mortgage Rate Protection Program (MRPP). This program will give an opportunity to purchase protection against sharp increases in mortgage rate. The author comments on the eligibility of homeowners, on the type of residence admissible, on the cost of protection, on the renewal, on the transfer possibility and describes how it will work and how long will the program apply.